Fitoremediasi Limbah Deterjen Menggunakan Tumbuhan Kiambang (Pistia stratiotes) Untuk Mengatasi Pencemaran Lingkungan - Tambunan, Cindy; Loise Tarigan, Beatrice; Marthin Pasaribu, Rio; Kristin Butarbutar, Anggun; Nilan Sari Rangkuty, Marlinda; Febriyossa, Adelia (Universitas Cokroaminoto Palopo, 2024)
Water pollution by detergent waste is a serious environmental problem because it contains chemical compounds such as phosphates and surfactants that are difficult to decompose. The Pistia stratiotes (kiambang) plant is a water weed that pools on the surface and is often used as an aquarium filler or as an interior ornament for water ponds. The benefits of aquatic plants such as kiambang can reduce the concentration of pollutants in waste through the phytoremediation process. This research aims to determine the ability of the kiambang plant (Pistia stratiotes) as a phytoremediation agent in reducing the level of water pollution and improving the quality of water exposed to detergent waste. The research method used was experimentation with variations in kiambang mass (50 g, 100 g, 150 g) in detergent wastewater samples. The research results show that the greater the mass of kiambang plants, the more effective it is in reducing water pH and improving water quality. The largest decrease in pH occurred in the treatment with a kiambang mass of 150 g after seven days, reaching an average pH value of 7.78. Phytoremediation with kiambang has been proven to be an environmentally friendly solution for managing detergent waste and helping restore aquatic ecosystems.